Revision of Alaptus (Hymenoptera: Mymaridae) in the Holarctic region, with taxonomic notes on some extralimital species - Triapitsyn, Serguei V. (Zootaxa, 2017)
The Holarctic species of Alaptus Westwood (Hymenoptera: Mymaridae) are revised and illustrated. An identification key to females of 17 species (16 named) is provided. The known distribution ranges are given, including new records of the extralimital specimens examined. Four newly described taxa are A. huberi sp. n. (Ontario, Canada), A. klonx sp. n. (Florida, Michigan and New York, USA), A. plih sp. n. (Sakhalin Island, Russia), and A. santetrapsi sp. n. (Far East of Russia as well as Alberta, Ontario and Yukon, Canada). The following new synonymies are proposed: A. extremus Soyka, syn. n., A. magnus Cheke & Turner, syn. n., and A. novickyi Soyka, syn. n. under A. fusculus Walker; A. priesneri Soyka, syn. n. under A. iceryae Riley; A. globosicornis variety hawaiiensis Girault, syn. n. and A. peregrinus (Perkins), syn. n. under A. globosicornis Girault; A. antillanus Cheke & Turner, syn. n. and A. caecilii Girault, syn. n. under A. immaturus Perkins; A. aegyptiacus Soyka, syn. n., A. auranti (García Mercet), syn. n., A. borinquensis Dozier, syn. n., A. intonsipennis Girault, syn. n., A. maccabei Girault, syn. n., A. maidli Soyka, syn. n., and A. malchinensis Soyka, syn. n. under A. minimus Westwood; Metalaptus torquatus Malenotti, syn. n. (from the previous synonymy under A. auranti), A. pechlaneri Soyka, syn. n., and A. psocidivorus Gahan, syn. n. under A. pallidicornis Foerster; A. globularis Sveum & Solem, syn. n. under A. schmitzi Soyka; and A. richardsi Hincks, syn. n. and A. tritrichosus Maláč, syn. n. under A. stammeri Soyka. Alaptus terebrans Kryger, stat. rev. is resurrected as a valid taxon from its previous synonymy under A. extremus, and A. globosicornis variety australiensis Girault is given species rank as A. australiensis Girault, stat. n. Lectotypes are designated for A. andersoni Ferrière, A. borinquensis, A. caecilii, A. eriococci Girault, A. foersteri Soyka, A. globosicornis, A. iceryae, A. malchinensis, A. pallidicornis, A. stammeri, Leimacis peregrinus Perkins, and Parvulinus auranti García Mercet; and neotypes are designated for A. excisus Westwood and A. immaturus. Taxonomic notes on six extralimital species of Alaptus are provided.